Sensitivity of panoramic radiographs in diagnosing maxillary sinusitis: a scoping review - Vera Widyastuti; Azhari Azhari; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The purpose of this study was to determine the sensitivity of using this panoramic radiograph in diagnosing maxillary sinusitis. Review: Scoping Review with article searches was carried out through NCBI's PubMed database, Science Direct, and EbscoHost from January 2020 to March 2021, with the inclusion criteria being articles published in 2010-2020. Conclusion: Panoramic radiographs were found to be less sensitive for diagnosing maxillary sinusitis, but due to the low availability and accessibility of CBCT and CT, and related to their expensive cost and high radiation, panoramic radiographs are considered to be quite optimal.